Controllable Synthesis of CoS2@N/S‐Codoped Porous Carbon Derived from ZIF‐67 for as a Highly Efficient Catalyst for the Hydrogen Evolution Reaction. Issue 4 (11th January 2018) - Feng, Shi; Li, Xingyue; Huo, Jia; Li, Qiling; Xie, Chao; Liu, Tingting; Liu, Zhigang; Wu, Zhenjun; Wang, Shuangyin
Abstract: A convenient, controllable method to fabricate an electrode is necessary to achieve the practical application of a hydrogen evolution reaction (HER) catalyst. In this work, an electrodeposition–ZIF conversion–sulfuration strategy is developed to produce a CoS2 @N/S‐codoped porous carbon (CoS2 @NSC/CFP) to drive the HER efficiently. CoS2 @NSC/CFP was prepared by the electrodeposition of Co(OH)2 on a carbon fiber paper followed by conversion into ZIF‐67 and subsequent sulfuration with sulfur. The loading of electroactive components can be controlled easily in the range of 0.7–10.0 mg cm −2 by varying electrodeposition time from 5 min to 2 h. The resulting material can be employed directly as a working electrode for the HER and it shows an excellent catalytic activity and stability with an overpotential of 95 mV at 10 mA cm −2 and 158 mV to reach 100 mA cm −2 in an acidic medium. The high efficiency is related intimately to the high dispersion of ultra‐small CoS2 nanoparticles, heteroatom‐codoping, and the 3 D porous network configuration of the carbon fiber paper. Abstract : Porous carbon electrode : CoS2 @N/S‐codoped porous carbon is prepared through an electrodeposition–ZIF conversion–sulfuration strategy. The loading of active sites can be controlled easily by varying the electrodeposition time. The resulting material can be employed directly as a working electrode for the hydrogen evolution reaction and shows an excellent catalytic activity and stability.